Sebutan Gaijin untuk Orang Asing: Sebuah Gambaran Bagaimana Orang Jepang Memandang Budayanya Sendiri - Wibowo, Robi; Putra, Heddy Shri Ahimsa; Simatupang, G.R. Lono (Universitas Diponegoro, 2023)
Foreigners in Japanese are called gaijin. There is debate among the Japanese themselves regarding the meaning of this word, some people do not interpret it negatively, some others say that the word should be avoided because it has a discriminatory meaning. This was then explored further in order to get an initial picture of the research. This study aims to describe how the term gaijin relates to the mindset of Japanese society. To achieve this goal, this research will reveal how the Japanese interpret the term gaijin. It also reveals the early history of the use of the term, and the relationship between the use of the term gaijin and the mindset of Japanese society. The theoretical assumption used in this study is the opinion of Sapir and Whorf which states that every society in a certain culture, with their own language codes, will represent the world in their own way. Research data were obtained from the internet and in- depth interviews with Japanese people. The results of the analysis show that the use of the term gaijin that they practice when referring to foreigners is not a conscious characterization, but is more appropriate to be understood as a linguistic representation that shows their own cultural ideology. The use of the term gaijin is not a representation of their awareness to directly discriminate against foreigners, but rather how the Japanese show their identity in viewing people outside of themselves and their group. <a href=